Task force: Gewerkschaften, Arbeitsmarktregulierung und Migration in China - Jann Christoph von der Pütten; Christian Göbel (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2013)
Die vorliegende Publikation untersucht die gegenwärtigen Entwicklungen am chinesischen Arbeitsmarkt. Sie analysiert die Funktion chinesischer Gewerkschaften und die Rolle von Tarifverhandlungen im Lohnfindungsprozess, aber auch die grundlegende Frage, ob Chinas Reservoir an billigen Arbeitskräften langsam versiegt. Einer genaueren Betrachtung wird auch die Situation der ca. 180 Millionen Wanderarbeiterinnen und Wanderarbeiter in China unterzogen. – – This publication traces current developments in the Chinese labor market. It analyses the function of Chinese trade unions and the role of collective bargaining for determining wage levels, and addresses the fundamental question if China is running out of cheap labour. The effect of recent legal changes on China's approximately 180 million migrant workers is also analysed in some detail, as are the specific challenges for female migrants.
Keywords: 330; China; Gewerkschaften; soziale Sicherung; Sozialversicherung; Wanderarbeiter; soziale Unruhe; Zivilgesellschaft; Gender; demografischer Wandel; Tarifverhandlungen; All-Chinesischer Gewerkschaftsbund; China; trade union; social security; social welfare; migrant workers; social unrest; civil society; gender; demographic change; collective bargaining; All-Chinese Federation of Trade Unions